Factors Influencing Consumers’ Intention to Buy on Sharia Insurance And The Implications Towards Maslaha: A Tawhidi String Relation (TSR) Approach - Fitriasari Sintarini; Akhmad Affandi Makhfudz (Indonesian Journal of Business, Accounting and Management (IJBAM), 2021)
The purpose of this study is to explain the factors that influence consumer’s intention to buy sharia insurance products. This study applies a qualitative methodology and uses Tawhidi String Relations (TSR) approach using The Koran and Sunnah as anthology in every solution in order to achieve maslaha/wellbeing (Maqashid Sharia). This study describe that knowledge, customer value, customer experience, technology, religiosity and trust have an influence to consumer intention to buy in sharia insurance products from the descriptive approach. The advantages of sharia insurance products need to be explained widely and properly. This study explores consumer’s intention to buy on sharia products can be arise by the blending the religious values into economic activity referring to The Koran and Hadith which are presented practically in the real world as a universally applicable basis in achieving Maqashid Sharia. The limitations of this study lie in the research area and the methodology used. Further research can be done in other research areas. The statistical test used can be enriched by using another research methods such as SEM-AMOS